Analysis of Company Performance and Its Influence Through Balanced Scorecard Using Intervening Variables of Work Climate in Medan City and Surrounding Areas - Rosita Rosita; Zulia Hanum; Julita Julita; Bunga Aditi; Ade Gunawan (Jurnal Manajemen Industri dan Logistik, 2023)
The purpose of the study was to measure the performance of  companies in the city of Medan and its surroundings with the implementation of the Balanced Scorecard (BSC) in order to increase competition through the intervening variable of the work climate that distinguishes each company. The research design is policy research using quantitative analysis techniques using the Lisrel application SEM, with a sample of 100. The calculation results of SEM analysis the work climate variable has an influence on company performance of 80.16%, while other variables that are not examined but also affect the lecturer's research performance are indicated by a value of 20%. The results showed that the measurement of company performance with BSC through its four perspectives, namely the Financial Perspective, Customers, Internal Business and Learning and Growth as well as through the intervening variable Organizational Climate, the results of which have a direct or indirect effect on the Company's performance.